Léčba dlouhodobých komplikací mechanické podpory funkce levé komory - Potapov, Evgenij V; Stepanenko, Alexander; Krabatsh, Thomas; Hetzer, Roland (Current opinion in cardiology (České vyd.), 2011)
As permanent support with ventricular assist devices (VADs) has become a reality and increasing numbers of patients are being supported for several years, the interactions between the VAD and the body and the management of complications during life-long support have gained the interest of clinicians and biomedical engineers. RECENT FINDINGS: Several interactions between the body and the implanted pump, including changes in the coagulation system, structure and function of the aortic valve, VAD-related infections, and technical failure as well as psychosocial aspects and their specific management have been described. SUMMARY: With enormous progress made in VAD technology, the incidence of complications has decreased over the years. However, with longer times of support, many aspects of the interaction between the implanted pump and the patient's body have been recognized. The management of these interactions and possible complications remain challenging, but it is possible to achieve long-term event-free VAD support.
Keywords: Catheterization; srdeční komory; Heart-Assist Devices; srdeční selhání; Thromboembolism; Risk Factors; Ventricular Dysfunction, Right; Hypertension, Pulmonary; dysfunkce pravé srdeční komory; aortální chlopeň; Hemodynamics; katetrizace; Time Factors; Aortic Valve; selhání zařízení; lidé; Heart Failure; Humans; časové faktory; rizikové faktory; podpůrné srdeční systémy; Heart Ventricles; Equipment Failure; hemodynamika; plicní hypertenze; tromboembolie